Discourse disctance and the swahili demonstratives - Timothy Wilt (LibraryPress@UF, 1987)
Proximity is the key concept for understanding a speaker's choice of Swahili demonstrative forms. The alternative approach in Leonard [1985] that proposes a speaker's concentration of attention as the key concept overlooks significant aspects of text structure. Proximity must not be conceived of, as does Leonard, only in terms of spatial distance between the speaker and a referent. Temporal, narrative, and anaphoric distance must also be considered.